Bonded vs. Vacuum-Formed Retainers: A Randomized Trial Assessing Stability, Longevity, and Patient Satisfaction - Charu Kasturia (Oral Sphere Journal of Dental and Health Sciences, 2026)
Background: Retention is a critical phase of orthodontic treatment, ensuring long-term stability of teeth and preventing relapse. Among commonly used retainers, bonded fixed retainers (BRs) and vacuum-formed retainers (VFRs) are widely prescribed, yet evidence regarding their comparative effectiveness remains limited. This randomized clinical trial aimed to compare stability, survival rate, and patient satisfaction between BRs & VFRs over a six-month retention period. Methods: A total of orthodontically treated patients were randomly allocated into two groups: BRs and VFRs. Stability was assessed using Little’s Irregularity Index (LII), intercanine width, intermolar width, and arch length at two-month intervals. Survival rates were recorded based on appliance failures, and patient satisfaction was evaluated using a structured questionnaire. Data were analysed using appropriate statistical tests with significance set at p < 0.05. Results: LII values increased significantly in the VFRs group after four and six months, while BRs showed significant changes in only at six months. Intercanine width, intermolar width, and arch length remained stable in both groups. Survival rates were high for both retainers, with BRs showing 98% (maxilla) and 97% (mandible), while VFRs showed 98% (maxilla) and 95% (mandible). Patient satisfaction was greater with BRs (90%) compared to VFRs (67%), with VFR users reporting higher discomfort and speech difficulties. Conclusion: Both BRs and VFRs demonstrated satisfactory survival rates, but BRs provided superior stability and greater patient satisfaction in the short-term retention phase. Long-term studies with larger samples are warranted.